Analisis faktor-faktor kesiapan bidan dalam pertolongan persalinan di era pandemi Covid-19 - Ida Listiana; Frida Kasumawati; Junaida Rahmi (Holistik Jurnal Kesehatan, 2022)
Background: In 2019, nearly 80 million women gave birth in health institutions globally. Pregnant women with comorbidities have a higher risk of serious illness, morbidity and mortality compared to the general population, the potential impact of the COVID-19 pandemic on mortality due to reduced access to maternal and infant health services. Midwives as the front line in MCH, family planning and reproductive health services, during the pandemic there were midwives independent practices that experienced closure of 9296 midwives, as many as 974 midwives. Every health service activity, including delivery assistance during the COVID-19 pandemic, midwives must provide services in accordance with health protocols, one of which is a place for delivery assistance. There are several factors that have a relationship with the readiness of midwives in providing care during childbirth, namely ability, experience, learning, rewards/reward, resources/equipment, attitude in service and perception of workload.Purpose: To determine the relationship between the factors of readiness of midwives in delivery assistance starting from the level of knowledge, attitudes, perceptions and sources of information. Method: The research design used is explanatory research. Population: all midwives who have a license to practice independent midwives in the South Tangerang City area, totaling at least 30 people using themethod purposive sampling. Data analysis was performed using a correlation test which measures the closeness of the relationship between two variables (correlation coefficient) using Chi Square.Results: There is a relationship between the level of knowledge and delivery assistance during the pandemic (p-value = 0.028 ), the perception of the midwife (p-value = 0.019), the attitude of the midwife (p-value = 0.09), there is no relationship between the source of information on the midwife with delivery assistance (p-value = 0.204),Conclusion: There is a relationship between the level of knowledge, attitudes, and perceptions of midwives on delivery assistance, but there is no relationship between information sources and delivery assistance during a pandemic. One of the causes is that health workers are not optimal in providing information about site selection and birth attendants during a pandemic.Keywords   : Midwife staff ; Service; Covid-19; PandemicPendahuluan: Pada tahun 2019, hampir 80 juta perempuan melahirkan di institusi kesehatan secara global. ibu hamil dengan komorbid memiliki risiko lebih tinggi untuk terjadinya penyakit berat, morbiditas dan mortalitas dibandingkan dengan populasi umum, potensi dampak pandemi COVID-19 terhadap kematian akibat berkurangnya akses ke layanan kesehatan ibu dan bayi. Bidan sebagai garda terdepan dalam pelayanan KIA, KB dan kesehatan reproduksi, di masa pandemi terdapat praktik mandiri bidan yang mengalami tutup dari 9296 bidan, sebanyak 974 bidan. setiap kegiatan pelayanan kesehatan termasuk dalam pertolongan persalinan selama pandemik covid-19 bidan harus memberikan pelayanan sesuai dengan protocol kesehatan, salah satunya adala Tempat pertolongan persalinan. Ada beberapa faktor yang mempunyai hubungan dengan kesiapan bidan dalam memberikan asuhan pada masa persalinan yaitu kemampuan, pengalaman, pembelajaran, penghargaan/imbalan, sumberdaya/peralatan, sikap dalam pelayanan dan persepsi tehadap beban kerja.Tujuan: Mengetahui hubungan faktor kesiapan bidan dalam pertolongan persalinan mulai dari tingkat pengetahuan, sikap, persepsi dan sumber informasi. Metode: Desain penelitian yang digunakan adalah explanatory research, Populasi: seluruh bidan yang memiliki ijin Praktik Bidan Mandiri di wilayah Kota Tangerang Selatan, berjumlah minimal 30 orang dengan menggunakan metode Purposive Sampling. Analisa data dilakukan dengan menggunakan uji korelasi yang mengukur keeratan hubungan antara dua variabel (koefisien korelasi) dengan menggunakan Chi Square.Hasil: Terdapat hubungan  tingkat pengetahuan dengan pertologan persalinan selama masa pandemic (p-value = 0,028 ), persepsi bidan (p-value = 0,019), sikap bidan  (p-value = 0,09 ), tidak terdapat hubungan antara sumber informasi bidan dengan pertologan persalinan  (p-value = 0,204),Simpulan: Terdapat hubungan tingkat pengetahuan, sikap, dan persepsi bidan terhadap pertolongan persalinan, tetapi tidak ada hubungan sumber informasi dengan pertolongan persalinan selama masa pandemic salah satu penyebabnya belum optimalnya tenaga kesehatan dalam memberikan informasi tentang pemilihan tempat dan penolong persalinan selama pandemic.